STACKING SEQUENCE OPTIMIZATION OF LAMINATE COMPOSITES USING HASHIN FAILURE CRITERIA - ONG, SZE KUAN (IRC, 2021)
The use of fibre-reinforced materials has become popular over the last two decades, particularly because of their high strength/weight ratio and also their potential to be redesigned to different design specifications by choosing the types of fibre materials used and their stacking orientation.